Interdental Bone Level around Immediately Placed Implants at Maxillary and Mandibular Molar Sites: A Retrospective Radiographic Analysis - Mohammed Alasqah; Khalid S. Alzahrani; Khalid Gufran (Medicina, 2023)
Background and Objectives: The current study aimed to compare the amount of interdental bone loss between early and immediate implant placements. Materials and Methods: A total of 16 immediate implants and 16 early implants radiographs were included in the current research. The bone level was assessed at two different stages: at the extraction appointment (T1) and after three to six months of implant placement (T2). A line was drawn from the cemento-enamel junction connecting adjacent teeth to the interdental line connecting the interdental alveolar crest at both stages. The difference between measurements in the T1 and T2 stages is the bone loss measurement for the early implant group. For the immediate implant placement sites, the measurements were taken from the interdental bone crest to the implant platform level. Results: A Mann–Whitney U test was performed to evaluate the differences between both groups. The descriptive statistics of the T1 and T2 stages for both groups suggest that the bone loss in the T2 stage was generally higher than T1 stage. The immediate implant group showed higher bone loss compared to the early implant group. Moreover, there was significantly higher bone loss (p = 0.039) in the immediate implant group compared to the early implant group. Conclusions: The results of this study indicate that immediate implant might have disadvantages over early implant in terms of bone loss after the extraction of maxillary and mandibular molar teeth.